FORUM KORDINASI PENANGGULANGAN TERORISME (FKPT) DAN GERAKAN DERADIKALISASI AGAMA DI INDONESIA: STUDI KASUS DI MALUKU - Abd. Rauf (IAIN Ambon, 2018)
One of the best ways to eradicate terrorism is through de-radicalization programs. Deradicalization is an attempt to neutralize radical notions for those involved in terrorists and their sympathizers and community members who have been exposed to radical understandings, through reeducation and resocialization and instilling multiculturalism. Strategic steps in the implementation and dissemination of de-radicalization programs in the regions are by involving Indonesian civil society organizations, given that the social environment is the main locus for the spread of seeds of radicalism. In this context the role of the Terrorism Prevention Coordination Forum (FKPT) has become very strategic. By involving FKPT as a public/civil society representation, the implementation of deradicalization programs has become more effective in the long term.